2001
DOI: 10.1074/jbc.m100998200
|View full text |Cite
|
Sign up to set email alerts
|

The Pyrimidine Ring-opened Derivative of 1,N 6-Ethenoadenine Is Excised from DNA by theEscherichia coli Fpg and Nth Proteins

Abstract: It was previously shown that 1,N 6 -ethenoadenine (⑀A) in DNA rearranges into a pyrimidine ring-opened derivative of 20-fold higher mutagenic potency in Escherichia coli (AB1157 lac⌬U169) than the parental ⑀A (Basu, A. K., Wood, M. L., Niedernhofer, L. J., Ramos, L. A., and Essigmann, J. M. (1993) Biochemistry 32, 12793-12801). We have found that at pH 7.0, the stability of the N-glycosidic bond in ⑀dA is 20-fold lower than in dA. In alkaline conditions, but also at neutrality, ⑀dA depurinates or converts into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…Since we and others have previously shown that ethenoadenine decomposes slowly into derivatives, which are not recognized by ANPG glycosylase, which excises ethenoA [62,63], and other ethenoadducts are also unstable, we have taken this into consideration during calculation of the results. In each experiment the negative control reaction without AlkB protein was performed, and percent of “repair” was calculated also for this negative control reaction.…”
Section: Methodsmentioning
confidence: 99%
“…Since we and others have previously shown that ethenoadenine decomposes slowly into derivatives, which are not recognized by ANPG glycosylase, which excises ethenoA [62,63], and other ethenoadducts are also unstable, we have taken this into consideration during calculation of the results. In each experiment the negative control reaction without AlkB protein was performed, and percent of “repair” was calculated also for this negative control reaction.…”
Section: Methodsmentioning
confidence: 99%
“…Aliquots were withdrawn at various times and quenched with 2 volumes of 0.3 M sodium hydroxide to obtain 0.2 M final concentration. The quenched samples were stored at 4 °C until further processed to prevent base-catalyzed ring-opening and subsequent depurination of the εA lesions (32). Samples were heated at 70 °C for 15 minutes to quantitatively cleave abasic sites.…”
Section: Methodsmentioning
confidence: 99%
“…UGI (uracil-DNA glycosylase inhibitor), a viral protein, has been shown to inhibit uracil-DNA glycosylase, which excises uracils in DNA generated from replication misincorporations (34). Speina et al (35) screened a battery of compounds including various base analogs and tryptophan pyrolysate (Trp-P-1), a mutagenic DNA intercalator heterocyclic amine found in cooked food, which targets a number of E. coli and human DNA glycosylases. The 2-thioxanthine was effective for E. coli Fpg protein and was shown to inhibit its excision activity whereas Trp-P-1 inhibits multiple DNA glycosylases such as AlkA, TagA, MPG, Nth, and Fpg by altering the DNA secondary structures (35).…”
Section: Discussionmentioning
confidence: 99%